Observing the Oceans in Real Time (Springer Oceanography,, 2018)
This book provides contributions from leading experts on the integration of novel sensing technologies to yield unprecedented observations of coupled biological, chemical, and physical processes in the ocean from the macro to micro scale. Authoritative entries from experts around the globe provide first-hand information for oceanographers and researchers looking for solutions to measurement problems. Ocean observational techniques have seen rapid advances in the last few years and this book addresses the need for a single overview of present and future trends in near real time and real time. First the past, present and future scenarios of ocean observational tools and techniques are elucidated. Then this book divides into three modes of ocean observations: surface, upper ocean and deep ocean. This is followed by data quality and modelling. Collecting a summary of methods and applications, this book provides first-hand information for oceanographers and researchers looking for solutions to measurement problems. This book is also suitable for final year undergraduate students or beginning graduate students in ocean engineering, oceanography and various other engineering students (such as Mechanical, Civil, Electrical, and Bioengineering) who are interested in specializing their skills towards modern measurements of the ocean.